2011
DOI: 10.1038/ijo.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight and weight change on normalization of prediabetes and on persistence of normal glucose tolerance in an older population: the KORA S4/F4 study

Abstract: Background and aims: In a population-based cohort study with older subjects and without specific interventions, we investigated the impact of body mass index (BMI) and BMI change (as well as waist circumference and change of waist circumference) on reversion from prediabetes to normal glucose tolerance (NGT) and on long-term persistence of NGT. Materials and methods: Oral glucose tolerance tests were conducted at baseline and at follow-up in a cohort study in Southern Germany (KORA S4/F4; 1223 subjects without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
5
15
1
Order By: Relevance
“…Our hypothesis was that consequences of CD start with increased BMI and later influence glucose, insulin, and consequently HOMA-IR and QUICKI regulation. Other studies have shown that metabolic disorders are preceded by BMI increases (38,39). This effect might explain why, in this population of young adults, we showed that CD was associated with increased BMI but not with other metabolic risk factors.…”
Section: Discussioncontrasting
confidence: 54%
“…Our hypothesis was that consequences of CD start with increased BMI and later influence glucose, insulin, and consequently HOMA-IR and QUICKI regulation. Other studies have shown that metabolic disorders are preceded by BMI increases (38,39). This effect might explain why, in this population of young adults, we showed that CD was associated with increased BMI but not with other metabolic risk factors.…”
Section: Discussioncontrasting
confidence: 54%
“…We observed an approximately 22% reversion rate in older adults over 12 years. The only other longitudinal population-based study of older adults to examine the reversion rate to normoglycaemia, the KORA S4/F4 study of 55-to 74-yearolds in Germany, found a reversion rate of 16.3% over 7 years of follow-up, using oral glucose tolerance test (OGTT) as diagnostic criterion [24]. We reported a slightly higher reversion rate of 16% during the first 6-year follow-up, which may be explained by a larger proportion of prediabetes diagnosed by HbA1c, as the sensitivity of HbA1c test in diagnosing prediabetes is inferior to the OGTT [25].…”
Section: Discussionmentioning
confidence: 99%
“…Heavy To our knowledge, only one observational study in older adults has investigated the association between weight change and normalization of glycaemia [24]. This study showed that weight loss, but not initial BMI, strongly increased the likelihood of reverting from prediabetes to normoglycaemia.…”
mentioning
confidence: 88%
“…The present results showed that combinations of current or maximum BMI and BMI changes greatly enhanced the identification of individuals with a high probability of having undiagnosed diabetes who could then be referred for further diagnostic testing. A prospective cohort study in Germany reported that reversion from pre-diabetes to normal glucose tolerance in older subjects was predicted by BMI reduction, but not by the initial BMI [27]. Further investigations are warranted to determine whether adding information on these BMI histories into common risk factors [26] of diabetes might refine the accuracy of screening for undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we observed that individuals with a relatively low current BMI, but having a higher BMI max or DBMI 20y-max , had a significantly lower prevalence of undiagnosed diabetes compared with individuals with high past BMI and high current BMI. A prospective cohort study in Germany reported that reversion from pre-diabetes to normal glucose tolerance in older subjects was predicted by BMI reduction, but not by the initial BMI [27]. Additionally, a clinical review has shown that changes in lifestyle are effective in preventing both diabetes and obesity in adults in the high-risk group who have impaired glucose tolerance [4].…”
Section: Discussionmentioning
confidence: 99%